2020
DOI: 10.13057/biodiv/d210752
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis and biodiversity of Lactic Acid Bacteria (LAB) on masin (fermented sauce) from Sumbawa, West Nusa Tenggara, Indonesia

Abstract: Abstract. Manguntungi B, Saputri DS, Mustopa AZ, Ekawati N, Afgani CA, Sari AP, Triratna L, Sukmarini L, Fatimah, Kusmiran A, Yanti S, Irawan S, Prasetyo MD, Fidien KA. 2020. Metagenomic analysis and biodiversity of Lactic Acid Bacteria (LAB) on masin (fermented sauce) from Sumbawa, West Nusa Tenggara, Indonesia. Biodiversitas 21: 3287-3293. Masin is a spontaneously fermented sauce from Sumbawa, West Nusa Tenggara Indonesia that is made of shrimp paste, chili, turmeric flower, and herbs mixed with some spices.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(32 reference statements)
0
2
0
1
Order By: Relevance
“…Previous research has found a broad spectrum of microorganisms in fermented fish products in Asia [24] , since different types of raw materials and fermentation conditions produce different microbiota. Meanwhile, when compared with masin products (fermented sauce made from shrimp paste, chilies, turmeric flowers, and other spices originating from Sumbawa, West Nusa Tenggara, Indonesia), the class of bacteria most frequently detected was the Enteroccocaceae family, genus Tetragenoccocus [14 , 25] . Previous studies reported that bacterial and yeast microbiota originating from Budu were able to increase feed digestibility and act as agents in inhibiting aflatoxins B1 [26 , 27] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has found a broad spectrum of microorganisms in fermented fish products in Asia [24] , since different types of raw materials and fermentation conditions produce different microbiota. Meanwhile, when compared with masin products (fermented sauce made from shrimp paste, chilies, turmeric flowers, and other spices originating from Sumbawa, West Nusa Tenggara, Indonesia), the class of bacteria most frequently detected was the Enteroccocaceae family, genus Tetragenoccocus [14 , 25] . Previous studies reported that bacterial and yeast microbiota originating from Budu were able to increase feed digestibility and act as agents in inhibiting aflatoxins B1 [26 , 27] .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, next-generation sequencing (NGS) is a tool that can be used for molecular identification, such as metagenomics, phylogenetics, and transcriptomics, which are currently applied to the cultural documentation of various samples. This method is well accepted as an accurate and reliable identification tool that can be used in the identification of microbial communities present in kimchi from Korea [9 , 10] , Godo, fermented soy from Japan [11] , Lemea, fermented bamboo shoots and fish from Indonesia [12] , Incwancwa, a traditional fermented cereal from Eswatini [13] , and Masin (salted sauce) in Sumbawa, West Nusa Tenggara, Indonesia [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu, pemanas dirancang sedemikian rupa untuk memperoleh temperatur fermentor tersebar merata pada seluruh bagian wadah penyimpanan masin. Temperatur optimal pada fermentor FERMAS-KECE adalah 37oC sesuai dengan temperature optimal fermentasi bakteri asam lactat (Nurdyansyah & Hasbullah, 2018) (Ayuti et al, 2016), dimana menurut (Manguntungi et al, 2020) bakteri asam laktat merupakan fermentasi yang mendominasi dalam proses fermentasi masin. Kapasitas produksi masin dengan fermentor FERMAS-KECE ini adalah 50 liter.…”
Section: Metode Kegiatanunclassified